Avaliação da dor e o seu processo de cuidado pós trauma cranioencefálico - Bomfim, Tássia Lima (2017)
Pain is a frequent symptom following Traumatic Brain Injury (TBI) and its experience should be better explored in the field of neuroscience. The aim of the study was to evaluate pain and their care process in adult patients after TBI. A cross-sectional quantitative research developed at the outpatient clinic of the Federal University of Sergipe (UFS) and emergency room of the Emergency Hospital of Sergipe (HUSE), after approval of the ethics committee.Data collection was carried out from August 2016 to May 2017, through interviews with the application form of the evaluation of pain were based on the functional health standards of Marjory Gordon, adapted by Pimenta and Cruz, which includes the McGill pain assessment questionnaire and Scales of verbal and numerical category, besides the analysis of the medical records of 40 patients with TBI. To evaluate the association between ordinal and nominal variables, the Rank-Bisserial correlation (Rrb) we used. The binomial test was applied to assess whether the proportion of cases that CTE pain affected Gordon's functional health standards. The significance level adopted was 5% and the software used was the R Core Team 2017. The results indicated that the patients were mostly young men who suffered TBI with hematoma due to the motorcycle accident and did not use equipments for individual protection.All patients evaluated with had pain ranging from moderate to unbearable or from moderate to severe on the verbal and numerical categories scales respectively. The most painful site in the body diagram was the head region. The descriptors of the most representative McGill questionnaire were the pain characterized as "Sickening", "Throbbing" and "Jumping". There was a shortage of record of the painful complaint in the medical record in the hospital, in contrast there was record of the pain in the totality of the medical records of the outpatient clinic. Most of patients with aggression, falls or other types of occurrence reported moderate pain, while victims of transport accidents presented severe or unbearable pain. Although, all patients had referred feeling pain, and daily life activities were not harmed. It is concluded that pain is a frequent symptom in the patient after the TBI, especially the headache and needs the evaluation of the health team, in order to provide a humanized and qualified care.